Porpomyces submucidus (Hydnodontaceae, Basidiomycota), a new species from tropical China based on morphological and molecular evidence - Wu, Fang; Zhao, Chang-Lin (Phytotaxa, 2015)
A new species is described from tropical China as Porpomyces submucidus on the basis of both morphological characters and molecular evidence. Phylogenetic analyse based on the ITS sequence, LSU sequence and the ITS+LSU sequence show that the new species belongs to Porpomyces and forms a distict clade as a sister group of Porpomyces mucidus. The fungus is characterized by thin, white to cream, resupinate basidiome with cottony to rhizomorphic margin, small pores (7–9 per mm), a monomitic hyphal structure with clamped generative hyphae, usually ampullated at most septa, and small, hyaline, thin-walled, ellipsoid basidiospores measuring 2.2–2.8 × 1.2–1.8 μm. It is closely related to Porpomyces mucidus, but the latter has larger pores (4–5 per mm) and larger basidiospores (2.8–3.9 × 2–2.8 μm).